Apoptosis and cell cycle arrest of human colorectal cancer cell line HT-29 induced by vanillin. - Ho, Ket Li; Saiful Yazan, Latifah; Ismail, Norsharina; Ismail, Maznah (Elsevier, 2009)
Background: Vanillin is responsible for the flavor and smell of vanilla, a widely used flavoring agent. Previous studies showed that vanillin could enhance the repair of mutations and thus function as an anti-mutagen. However, its role in cancer, a disease that is closely related to mutation has not yet been fully elucidated.